Nanostrontium ranelate incorporated injectable hydrogel enhanced matrix production supporting chondrogenesis in vitro. Issue 23 (18th May 2016) - Deepthi, S.; Abdul Gafoor, Amna A.; Sivashanmugam, A.; Nair, Shantikumar V.; Jayakumar, R.
Abstract : An injectable strontium ranelate nanoparticle-loaded composite gel provides a required environment for chondrogenesis, supplemented with the controlled release of strontium ranelate. Abstract : An injectable hydrogel, with the advantage of adaptability to defect sites, patient compliance, controlled flowability and high water uptake capability, was explored as a prototype for cartilage tissue regeneration. Chitosan and fibrin are natural biomaterials that are biocompatible, biodegradable, resemble the ECM of the tissues and contain cell adhesion sites thereby providing a support for cell growth. In this study strontium ranelate, a drug recently studied to enhance cartilage regeneration, was encapsulated in chitosan nanoparticles to provide sustained delivery of the drug content within the composite gel (chitosan/alginate/fibrin hydrogel). The developed nanocomposite gel was characterized using SEM, EDS and FTIR. The particle size of the strontium ranelate loaded chitosan nanoparticles was found to be 160 ± 30 nm. The encapsulation and loading efficiency values of strontium ranelate were found to be 40 ± 10% and 36 ± 2% respectively. Rheological data showed a storage modulus of 5.514 ± 0.102 kPa with thermal stability over the studied temperature range, and the gel properties could be restored within 10 s after the application of a high shear rate. The cytocompatibility and chondrogenic potential was analyzed using human mesenchymal stem cells (hMSCs) to evaluate the applicability of the developed hydrogel for cartilage regeneration. hMSCs were found to be viable in the developed hydrogels and chondrogenic differentiation of hMSCs was observed which was confirmed with enhanced proteoglycan and collagen synthesis. These results indicated that the developed injectable nanocomposite gel would be a suitable system for cartilage regeneration.